Comparative Analysis Of Financial Performance Before And After The Acquisition Of The PT. Fajar Surya Wisesa Tbk - Saputro, Ricki Eko; Murwanti, Sri (Journal of Applied Management Research, 2024)
In business, expansion is an action taken to widen one's business or extend influence. One strategy for expansion is through acquisition. This strategy was employed by Siam Cement Group (SCG) from Thailand, which officially acquired 55% of the shares of PT. Fajar Surya Wisesa. Based on this, an analysis is needed to determine whether there are differences in financial performance. The method used is quantitative, utilizing six financial ratios as indicators: ROA, ROE, NPM, TATO, CR, and DER. Data was collected from PT. Fajar Surya Wisesa's financial reports during the period before acquisition from the first quarter of 2015 to the third quarter of 2019, as well as the period after acquisition from the fourth quarter of 2019 to the third quarter of 2023. The analysis method involves normality testing and non-parametric Wilcoxon test. The final analysis indicates that the ROA, ROE, NPM, and CR ratios experienced differences after acquisition, while TATO and DER ratios did not show significant differences. Therefore, it can be interpreted that the acquisition strategy carried out by Siam Cement Group (SCG) on PT. Fajar Surya Wisesa is quite effective.